Penggantian Sebagian Ransum Komersil oleh Jagung dan Pengaruhnya terhadap Kualitas Fisik Daging Broiler - Mega, Olfa; Brata, Bieng; Setianto, Johan (Fakultas Peternakan Universitas Jambi, 2016)
The study aimed to evaluate the physical quality of broiler meat that give commercial ration partially substituted by corn. The study used 80 broiler chickens aged 21 days. Chicken is divided into 4 (four) groups of body weight as replicates, each group consisted of 5 replicates chickens. The treatments were given in this study consisted of substitution of 0%, 10, 20% and 30% by commercial ration of corn. The results showed that the use of corn as a substitute for commercial ration significantly (P <0.05) to the water holding capacity, cooking loss and meatbone ratio, but not significant (P> 0.05) on the pH value of the meat. Water holding capacity on the use of corn 30% (34.40%) is significantly higher than the use of maize 0% (15.7%), 10% (22.33%) and 20% (23.78%). Water holding capacity on the use of corn 10% and 20% in commercial diet showed no significant difference. Cooking loss meat on the use of corn 30% (26.32%) is lower than the use of maize 0% (39.47%), 10% (34.21%) and 20% (36.11%), while the meatbone ratio treatment 10% corn (3.83) is higher than the treatment 20% and 30% corn. The range of pH values ​​in this study was 6.5 to 6.8 with the average of 6.63. Substitution of commercial rations by as much as 30% corn gives the value of the high water holding capacity and low cooking loss, while meatbone ratio highest found in 10% of substitution treatment. Keywords: physical quality, broiler meat, corn